Daily profiles of steroid hormones and their metabolites related to food intake - Rácz, B; Dušková, M; Vondra, K; Šrámková, M; Hill, M; Stárka, L (Physiological research, 2015)
The aim of this study was to look for changes in the daily profile of steroid hormones after standardized food intake. Eight young women not taking contraceptives were followed from 5:30 a.m. till 9:30 p.m. before and 1 and 2 h after eating breakfast, snack, lunch, the second snack and dinner. The differences in steroid levels before and after meals were evaluated. As expected, glucose, C-peptide and ghrelin levels changed postprandially. The steroid hormones cortisol, progesterone, pregnenolone and dehydroepiandrosterone showed a decrease after main meals, whereas testosterone and dihydrotestosterone showed no significant dependence on food intake. Estrogen levels did not exhibit a significant nycthemeral rhythm, but estradiol decreased after main meals. In our study the known nycthemeral rhythm of LH, FSH, cortisol, progesterone and pregnenolone after food intake were confirmed, but significant changes after meals were also observed in the levels of cortisol, dehydroepiandrosterone, estradiol and SHBG.
Keywords: Progesterone; ghrelin; přijímání potravy; Adult; dehydroepiandrosteron; Sex Hormone-Binding Globulin; dospělí; Eating; hydrokortison; cirkadiánní rytmus; Hydrocortisone; Circadian Rhythm; Estradiol; lidé; ženské pohlaví; Humans; progesteron; Dehydroepiandrosterone; pregnenolon; Ghrelin; Female; Pregnenolone; estradiol; globulin vázající pohlavní hormony